2004
DOI: 10.1091/mbc.e03-08-0596
|View full text |Cite
|
Sign up to set email alerts
|

Association with Membrane Protrusions Makes ErbB2 an Internalization-resistant Receptor

Abstract: In contrast to the epidermal growth factor (EGF) receptor, ErbB2 is known to remain at the plasma membrane after ligand binding and dimerization. However, why ErbB2 is not efficiently down-regulated has remained elusive. Basically, two possibilities exist: ErbB2 is internalization resistant or it is efficiently recycled after internalization. By a combination of confocal microscopy, immunogold labeling electron microscopy, and biochemical techniques we show that ErbB2 is preferentially associated with membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
202
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(245 citation statements)
references
References 45 publications
38
202
2
3
Order By: Relevance
“…The preferred ErbB2 dimer partner increases ligand-binding affinity (Karunagaran et al, 1996) and reduces EGF dissociation to prolong signal activation. Heterodimers containing ErbB2 are also more stable and endocytosed at lower rates than other ErbB dimers (Lenferink et al, 1998;Wang et al, 1999;Hommelgaard et al, 2004). Thus, signalling via ErbB1/2 heterodimers may be more powerful and sustained than that arising via ErbB1 homodimers.…”
Section: The Egfr Familymentioning
confidence: 99%
“…The preferred ErbB2 dimer partner increases ligand-binding affinity (Karunagaran et al, 1996) and reduces EGF dissociation to prolong signal activation. Heterodimers containing ErbB2 are also more stable and endocytosed at lower rates than other ErbB dimers (Lenferink et al, 1998;Wang et al, 1999;Hommelgaard et al, 2004). Thus, signalling via ErbB1/2 heterodimers may be more powerful and sustained than that arising via ErbB1 homodimers.…”
Section: The Egfr Familymentioning
confidence: 99%
“…The cells with higher HER2 expression showed significantly higher trastuzumab-mediated cytolysis (data not shown). The results are expressed as mean of three independent experiments , others have not (Austin et al, 2004;Hommelgaard et al, 2004;Longva et al, 2005). Interestingly, in some of the models that have not observed trastuzumabmediated receptor downregulation (Austin et al, 2004;Longva et al, 2005), there is also a lack of trastuzumabinduced HER2 phosphorylation.…”
Section: Effects Of Lapatinib and Trastuzumab On Bt474 Xenograftsmentioning
confidence: 99%
“…A key regulator of HER receptor degradation is the E3 ubiquitin ligase c-Cbl (Marmor and Yarden, 2004). Although E3 ubiquitin ligase c-Cbl shows only a marginal effect in ligand-induced HER2 ubiquitination (Wang et al, 1999;Hommelgaard et al, 2004), it does play a role in receptor degradation when c-Cbl is overexpressed or recruited following treatment with anti-HER2 antibodies (Klapper et al, 2000;Wolpoe et al, 2003). However, we cannot rule out that the internalization of HER2 following trastuzumab treatment could be mediated by a kinase-dependent activation of other ubiquitin ligases.…”
Section: Effects Of Lapatinib and Trastuzumab On Bt474 Xenograftsmentioning
confidence: 99%
“…Little attention has been paid to the role of ErbB2 degradation in cancers, although when compromised it also would lead to increased ErbB2 levels and activity. Several studies have shown that endocytic downregulation of ErbB2 is impaired in cancer cells (Sorkin et al, 1993; Baulida et al, 1996;Wang et al, 1999;Hommelgaard et al, 2004;Austin et al, 2004;Longva et al, 2005), and ErbB2 can even transmit this property to the related epidermal growth factor receptor (EGFR; Muthuswamy et al, 1999;Wang et al, 1999;Worthylake et al, 1999;Haslekas et al, 2005). Inhibition of HSP90 (e.g., with geldanamycin [GA]) leads to increased internalization and lysosomal degradation of ErbB2 in a manner depending on proteasomal activity (Tikhomirov and Carpenter, 2000;Austin et al, 2004;Lerdrup et al, 2006).…”
mentioning
confidence: 99%
“…After a wash the cells were next incubated with mouse monoclonal Sc08 (Santa Cruz Biotechnology) against the extracellular (N-terminal) part of ErbB2, followed by 5-nm gold-labeled goat anti-mouse antibody (Amersham Biosciences). After a brief fixation and a wash the cells were scraped off and further processed for Epon embedding and electron microscopy (pre-embedding immunogold labeling electron microscopy) as previously described (Hommelgaard et al, 2004). …”
mentioning
confidence: 99%